Intubation with transillumination: nasal or oral? - Petroianu, Georg; Subotic, S.; Heil, P.; Jatzko, A.; Maleck, W. H. (Prehospital and disaster medicine, 1999)
Transillumination-guided intubation is a useful back-up method when laryngoscopic intubation proves to be difficult or impossible. The Trachlight™ (Laerdal, N-4001 Stavanger, Norway) is suited for both nasal and oral use. Intubation times (intubation time) and success rates (success rate) for nasal and oral intubation with the Trachlight were compared.Twenty-four medical students, inexperienced in intubation were instructed in the use of the Trachlight. A demonstration also was performed. Subsequently, they were asked to intubate a Laerdal Airway Management Trainer™ (Laerdal, Stavanger, Norway) using the Trachlight. Each student intubated 10 times orally and 10 times nasally (five times through the right and five times through the left nostril). The succession of the students was randomized The intubation times were measured and the position of the tube noted. Nasal and oral intubation times for the tenth trial (steady state conditions) were compared using the rank-order test for paired observations. Oral and nasal success rates were compared using the sign test for paired observations.The differences between nasal and oral intubation concerning intubation time and the success rates were not significant. Nasal intubation with the Trachlight seems to be more difficult than the oral intubation.